Overset LES for trailing-edge noise computations - Paul Bernicke and Rinie Akkermans and Roland Ewert and Jürgen Dierke (Curran Associates, Inc., 2017)
In this paper a hybrid Zonal LES tool is applied to trailing-edge noise. The so-called “Overset” analysis represents a non-linear perturbation analysis on top of a steady background flow (the latter typically obtained from a steady RANS solution). The non-linear Euler equations are extended with viscous terms and therefore represent full Navier-Stokes equations in disturbance form. The important aspect of inflow turbulence, common to all hybrid RANS/LES methods, is tackled with the aid of the Fast Random Particle-Mesh method (FRPM). FRPM generates artificial turbulence whose statistics match that of the underlying RANS. The stochastic turbulence is subsequently injected into the Overset LES simulation via the eddy-relaxation source term. A 3D NACA0012 Overset LES covering a restricted regime around the trailing edge itself acts as a prove of concept for the de- sired trailing-edge noise study. The given results are supplemented by a 2D aeroacoustic trailing-edge noise analysis that yield promising results and furthermore, illustrates that the eddy-relaxation term is acoustically transparent.